Effects of tumor necrosis factor (TNF) gene polymorphisms on the association between smoking and lung function among workers in swine operations. Issue 13 (3rd July 2021) - Gao, Zhiwei; Dosman, James A.; Rennie, Donna C.; Schwartz, David A.; Yang, Ivana V.; Beach, Jeremy; Senthilselvan, Ambikaipakan
ABSTRACT: Workers in swine operations may be at increased risk of developing respiratory problems. These respiratory conditions are more prevalent among workers who are smokers. Tumor necrosis factor ( TNF ) genes play an important role in human immune responses to various respiratory hazards. This study aimed to investigate whether polymorphisms in TNF genes might alter the effects of smoking on lung function among workers in swine operations. Three hundred and seventy-four full-time workers from large swine operations and 411 non-farming rural dwellers in Saskatchewan were included in this study. Information on demographic and lifestyle characteristics, pulmonary function, and blood samples were obtained. Multiple linear regression analyses were used in the statistical analysis. Three promoter polymorphisms ( rs1799724, rs361525, and rs1800629 ) in the TNF gene were investigated. Only the interaction term between smoking status and rs1799724 was significant in the multiple regression models. Among workers with the rs1799724 polymorphism (TT+TC), current smokers exhibited significantly lower lung function than nonsmokers. These associations were not observed among workers with the wild-type (CC). These findings were not observed among non-farming rural dwellers. Data demonstrated the possible involvement of TNF gene in (1) development of adverse respiratory conditions among workers who are smokers, (2) importance of smoking cessation among workers, especially those with polymorphisms in the TNF gene, and (3) potential implications in treatment, screening, and prevention.